2022
DOI: 10.48550/arxiv.2204.02986
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High Equivalent Width of Hα+[N II] Emission in z~8 Lyman-break Galaxies from IRAC 5.8μm Observations: Evidence for Efficient Lyman-continuum Photon production in the Epoch of Re-ionization

Mauro Stefanon,
Rychard J. Bouwens,
Garth D. Illingworth
et al.

Abstract: We measure, for the first time, the median equivalent width (EW) of Hα+[N II] in star-forming galaxies at z ∼ 8. Our estimate leverages the unique photometric depth of the Spitzer /IRAC 5.8µmband mosaics (probing ≈ 5500 − 7100 Å at z ∼ 8) of the GOODS Reionization Era Wide Area Treasury from Spitzer (GREATS) program. We median stacked the stamps of 102 Lyman-break galaxies in the 3.6, 4.5, 5.8 and 8.0µm bands, after carefully removing potential contamination from neighbouring sources. We infer an extreme rest-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 96 publications
(180 reference statements)
2
6
0
Order By: Relevance
“…By combining HST and Spitzer photometry for large samples at 𝑧 6, the bulk integrated properties of the population ★ E-mail: zychen@email.arizona.edu have been established (see Stark 2016 for a review), revealing relatively low stellar masses ( 10 10 M ), large specific star formation rates ( 5 − 10 Gyr −1 ) and blue UV continuum slopes (𝛽 = −2) indicative of minimal dust reddening. Collectively these observations are consistent with reionization-era galaxies undergoing rising star formation histories, leading to rapid mass growth and typical light-weighted stellar ages of 50-200 Myr (e.g., Laporte et al 2021;Whitler et al 2022;Stefanon et al 2022).…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…By combining HST and Spitzer photometry for large samples at 𝑧 6, the bulk integrated properties of the population ★ E-mail: zychen@email.arizona.edu have been established (see Stark 2016 for a review), revealing relatively low stellar masses ( 10 10 M ), large specific star formation rates ( 5 − 10 Gyr −1 ) and blue UV continuum slopes (𝛽 = −2) indicative of minimal dust reddening. Collectively these observations are consistent with reionization-era galaxies undergoing rising star formation histories, leading to rapid mass growth and typical light-weighted stellar ages of 50-200 Myr (e.g., Laporte et al 2021;Whitler et al 2022;Stefanon et al 2022).…”
Section: Introductionsupporting
confidence: 73%
“…The internal structure of 𝑧 6 galaxies, with most of the stellar mass locked in bright star forming complexes, points to a rapid phase of mass assembly, consistent with the large sSFR expected at these high redshifts (e.g., Topping et al 2022;Stefanon et al 2022;Leethochawalit et al 2022). The presence of multiple clumpy components separated by <1 to 4 kpc (and asymmetric single components) suggests merger activity may be common, as suggested by pair counts (Duncan et al 2019).…”
supporting
confidence: 61%
“…Deep multi-wavelength imaging surveys have been at the forefront of studies of galaxy formation at high redshift. The sensitivity and large sample sizes comprising such surveys have utilized models of the integrated spectral energy distributions (SEDs) produced by galaxies to infer many key properties of the galaxy population, including stellar masses, stellar population ages, star-formation histories, and strengths of strong nebular emission lines (e.g., Ono et al 2012;Labbé et al 2013;Smit et al 2014;Bouwens et al 2014Bouwens et al , 2015Finkelstein et al 2015;Roberts-Borsani et al 2016;Stark 2016;De Barros et al 2019;Endsley et al 2021;Stefanon et al 2022). New datasets from the James Webb Space Telescope ( JWST) will soon dramatically advance the available sample sizes and measurement precision probing galaxies in the earliest epochs.…”
Section: Introductionmentioning
confidence: 99%
“…Rapidly growing seed BHs are characterized by extremely red infrared colors caused by the flat continuum of the BH radiation and strong Hα emission. As demonstrated in Figure 3, accreting seed BHs tend to be redder compared to the other three cases at the same redshift range and thus can be distinguish-3 Recently, Stefanon et al (2022) reported an extremely high value of EW Hα rest 1960 +1089 −927 Å in z ∼ 8 star-forming galaxies by stacking the image stamps of 102 Lyman-break galaxy candidates. The median-staked SED with a blue UV slope (α λ −2.4) and enhanced flux densities at λ obs = 3.6 and 4.5 µm could be explained by the contribution of a star-forming galaxy with Z > 0.1 Z and an accreting seed BH.…”
Section: Photometric Color Selectionmentioning
confidence: 94%